EFEK KONSENTRASI LARUTAN NaCl TERHADAP KEMAMPUAN FOTOREAKTOR HEKSAGONAL BERBASIS PLAT CuO/Al - Afria Yolanda; Rahadian Zainul (Departemen Kimia FMIPA UNP, 2020)
A solar cell (photovoltaic cell) is a device that has the ability to convert sunlight energy into electrical energy by applying the photovoltaic principle. The photovoltaic principle is defined as a phenomenon of the appearance of an electric voltage due to the contact of two electrodes connected to a solid or liquid system when exposed to sunlight. This study aims to determine the maximum power generated from the photoreactor, determine the effect of concentration variations and determine the efficiency of the photoreactor. The method in this study is an experiment using photovoltaic cells in the form of a hexagonal photoreactor with a size of 3x70x400 mm and a concentration variation of 0.25; M 0.5 M; 0.75 M; and 1 M. The variables in this study were the time of measurement and concentration. Current and voltage measurements are carried out 5 hours a day for 3 days of measurement. The results showed that the optimum concentration of sodium chloride was at a gelation concentration of 0.75 M. The measurement time that produced the maximum power was at 13.00 WIB, then the stability of the solar cells on day 2.The maximum power obtained was 0.0288 mWatt and the ability of the electrodes to produce electricity per area is 11.8907 mWatt / m2 with a cross-sectional area of the electrode used is 0.0183 m2. And the maximum efficiency obtained is 1.0034%. From the research results obtained: The greater the concentration of sodium chloride, the greater the power produced